Identifying global and local drivers of change in mangrove cover and the implications for management - J. M. Maina; J. O. Bosire; J. G. Kairo; S. O. Bandeira; M. M. Mangora; C. Macamo; H. Ralison; G. Majambo (Global Ecology and Biogeography, 2021)
Background Climate change and human activities continue to drive a widespread decline in global mangrove coverage, undermining their capacity to provide ecosystem benefits. While global and local scale drivers of change on mangroves are widely acknowledged, the relative importance and the exposure of mangroves to climatic, geomorphological, and direct human threats vary spatially. Understanding the role and relative importance of the multiscale and multiple threats to mangroves and how these vary spatially is fundamental for formulating a spatially adaptive approach to their management and conservation. Aim Our study investigated the role of multiple threats on mangroves and the relative exposure. Location Western Indian Ocean (WIO) region. Time period Recent past (2002–2019 and future (2050–2060). Major taxa studied Mangrove. Methods Using satellite‐derived indicators of mangrove condition aggregated over 19 years (2002 to 2019) and 14 proxies of climate, human activity, and geomorphology, we applied machine learning methods to determine the role and relative importance of the change drivers. Using outputs from this deductive statistical process, we applied inductive methods to map mangrove exposure spatially. Results Model results highlight the importance of catchment erosion, human pressure, sea level, and macroclimate as the main drivers of the present‐day ecological condition of mangroves in the WIO. Normalized difference vegetation index (NDVI) was more sensitive to the identified drivers than the vegetation condition index (VCI), with the relative importance of variables varying across the two vegetation indicators. Main conclusions In anticipation of a stronger manifestation of climate change impacts, the resilience of mangroves in the WIO could be improved through adaptive management over time and space. Testing the efficacy of the essential biodiversity variables (EBV) is critical for understanding the mechanisms of ecosystem change and managing biodiversity change.